THE FACTOR THAT DETERMINES PERSONAL COMPETENCE IN ADOLESCENT PERIOD OF LIFE CONTENT (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article examines the impact of life goals on the development of personal potential during adolescence. At the same time, the analysis of the theoretical approaches of scientists regarding the purpose of the meaning of life during adolescence is described. In particular, it was possible to examine the problem of interrelationship between the development of personal potential and the goal of the meaning of life during adolescence.